Thermal Solution for Kerosene Crude Oil by Kirkuk Molecular Sieves - Ragheed Ghazal (College of Education for Pure Sciences, 2006)
The study included upgrading kerosene of kirkuk crude oil by performing catalytic cracking for kerosene in vapor phase over molecular selves (5A°) as catalyst at temperatures of (400,500,550 and 600)°C ,using thermally controlled tubal furnace. The structural conversions of treating kerosene samples were studied by measuring the ratio of olefinic, aromatic, and n-paraffmic compounds, beside the measurements of distillation curves, refractive index and density, and finally infrared spectroscopy (IR). The process showed the ability of catalyst to proceed through catalytic cracking involving olefins, structural conversions and dehydrogenation processes .The olefins amount increased up to (7.914%) at (600)°C Compared with(0.211%)in untreated kerosene, aromatic compounds reached to (20.3%) of the total at (550°C) and finally the ratio of n-paraffins compounds increased upto(35.4%)at(500)°C.